Pentraxin 3 is an adipose tissue‐related serum marker for pancreatic cancer cachexia predicting subsequent muscle mass and visceral fat loss. Issue 12 (12th October 2022) - Sato, Katsuhiko; Hikita, Hayato; Shigekawa, Minoru; Kato, Seiya; Sasaki, Yoichi; Shinkai, Kazuma; Fukuoka, Makoto; Kudo, Shinnosuke; Sato, Yu; Fukumoto, Kenji; Shirai, Kumiko; Myojin, Yuta; et al.
Abstract: Cancer cachexia, a paraneoplastic syndrome characterized by ongoing skeletal muscle mass loss, is accompanied by adipose tissue loss and strongly affects chemotherapy endurance. Our aim was to detect a serum marker reflecting pancreatic cancer cachexia and predicting subsequent loss of muscle mass and adipose tissue, focusing on adipose tissue‐secreted proteins. Murine‐derived pancreatic cancer cells were orthotopically injected into the mouse pancreatic tail. After 3 weeks, RNA sequencing of perigonadal fat and orthotopic tumors was carried out. We analyzed stocked sera and clinical data of metastatic pancreatic cancer patients who received chemotherapy. Perigonadal fat weight/body weight decreased in mice with orthotopic tumors compared to those without tumors. By RNA sequencing and real‐time PCR validation, pentraxin 3 ( PTX3 ) was identified as a secreted protein‐encoded gene whose expression was significantly higher in the perigonadal fat of mice with orthotopic tumors than in that of mice without orthotopic tumors and was least expressed in orthotopic tumors. Serum PTX3 levels correlated with PTX3 mRNA levels in perigonadal fat and were higher in mice with orthotopic tumors than in those without tumors. In 84 patients diagnosed with metastatic pancreatic cancer, patients with high serum PTX3 levels showed a greater visceral fat loss/month and skeletal muscle mass index (SMI) decrease/month than those with low serum PTX3 levels. High serum PTX3 was an independent risk factor for visceral fat loss, decreased SMI, and poor prognosis. High serum PTX3 in pancreatic cancer patients predicts visceral fat and muscle mass loss and major clinical outcomes of cancer cachexia. Abstract : Serum pentraxin 3 (PTX3) level, which correlated with adipose tissue‐produced PTX3 level, was identified as a candidate marker for cancer cachexia by using mice with orthotopic pancreatic cancer. In patients with metastatic pancreatic cancer, high serum PTX3 was an independent risk factor for visceral fat loss, decreased skeletal muscle mass index, and poor prognosis. Collectively, we clarified that serum PTX3 is a novel adipose tissue‐related marker for pancreatic cancer cachexia predicting subsequent muscle mass and visceral fat loss.